2019
DOI: 10.3389/fpls.2019.00061
|View full text |Cite
|
Sign up to set email alerts
|

Association Study Reveals Genetic Loci Responsible for Arsenic, Cadmium and Lead Accumulation in Rice Grain in Contaminated Farmlands

Abstract: Accumulation of toxic heavy metals and metalloids (THMMs) in crop grain remarkably affects food safety and human health. Reducing the content of THMMs in grain requires the identification and manipulation of the genes regulating their accumulation. This study aimed to determine the genetic variations affecting grain THMM accumulation in rice by using association mapping. We used 276 accessions with 416 K single nucleotide polymorphisms (SNPs) and performed genome-wide association analysis of grain THMM concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 70 publications
0
27
0
Order By: Relevance
“…Together, it is plausible that GCC7 has a capacity to interact with qGCd7.1 regulating the Cd uptake. Using genome-wide association studies, Liu et al [61] reported 17 QTLs associated with grain Cd concentration. Among them, a novel candidate gene encoding OsARM1, a MYB transcription factor, previously known as responsible for freezing tolerance [62][63][64], was predicted to respond to Cd stress.…”
Section: Current Trends In Breeding Programsmentioning
confidence: 99%
“…Together, it is plausible that GCC7 has a capacity to interact with qGCd7.1 regulating the Cd uptake. Using genome-wide association studies, Liu et al [61] reported 17 QTLs associated with grain Cd concentration. Among them, a novel candidate gene encoding OsARM1, a MYB transcription factor, previously known as responsible for freezing tolerance [62][63][64], was predicted to respond to Cd stress.…”
Section: Current Trends In Breeding Programsmentioning
confidence: 99%
“…Genome-wide association study (GWAS) can overcome these two limitations and is a powerful tool to identify genome regions associating with complex traits 27 , 28 . Through a GWAS of 276 diverse accessions, 60 QTLs were detected for accumulation of arsenic, cadmium, and lead in rice 29 . Zhao et al 30 identified 14 QTLs associated with Cd accumulation in rice by GWAS and predicted OsNRAMP2 as the candidate gene of qCd3–2 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also demonstrated that HvCBT1 (CaM binding transporter) in barley, AtCNGC1 (cyclic nucleotide-gated ion channel) in Arabidopsis and NtCBP4 in tobacco, as one of the nonselective entry pathways used by Pb [28][29][30][31]. For further exploring genetic factors responding to Pb stress, Genome-wide association study (GWAS), a powerful tool to detect the genetic architecture of complex traits, has been widely used in rice, maize and grasses [12,[32][33][34][35][36][37][38][39]. GWAS has also been used to study HMs concentration, tolerance to Cd and other abiotic stress related quantitative trait loci (QTLs), but not the molecular mechanism of Pb tolerance in B. napus [23,[40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%